Human Dental Pulp Stem Cells and Gingival Fibroblasts Seeded into Silk Fibroin Scaffolds Have the Same Ability in Attracting Vessels - Woloszyk, Anna; Buschmann, Johanna; Waschkies, Conny; Stadlinger, Bernd; Mitsiadis, Thimios A. (Frontiers in Physiology, 2016)
Neovascularization is one of the most important processes during tissue repair and regeneration. Current healing approaches based on the use of biomaterials combined with stem cells in critical-size bone defects fail due to the insufficient implant vascularization and integration into the host tissues. Therefore, here we studied the attraction, ingrowth, and distribution of blood vessels from the chicken embryo chorioallantoic membrane into implanted silk fibroin scaffolds seeded with either human dental pulp stem cells or human gingival fibroblasts. Perfusion capacity was evaluated by non-invasive in vivo Magnetic Resonance Imaging while the number and density of blood vessels were measured by histomorphometry. Our results demonstrate that human dental pulp stem cells and gingival fibroblasts possess equal abilities in attracting vessels within silk fibroin scaffolds. Additionally, the prolonged in vitro pre-incubation period of these two cell populations favors the homogeneous distribution of vessels within silk fibroin scaffolds, which further improves implant survival and guarantees successful healing and regeneration.